RANCANGAN BOOKING SERVICE ONLINE PADA PT. SABANG RAYA MOTOR JAMBI: Application, booking, online, PHP, Menu service, system. - Susanto, Darex (LP2M Universitas Nurdin Hamzah, 2017)
With the widespread use of the internet in various fields then the information needs No longer limited by distance and time. In addition to providing information, the internet can also be used to conduct online transactions. This makes it easier for the user to do online transactions the user does not have to be where the transaction occurred. Current online transactions are not only used in the business world to sell products, but also used in the field of services for example is booking a place / slot for the service of two-wheeled vehicles online based on the web. Online Booking Service Online Booking Yamaha Jambi Central departs from the vision, mission and purpose of the dealer. That is to be a qualified Yamaha dealer in providing the best service for consumers. This final project will describe the activities and products produced at each stage of development. Design information booking system includes input data for consumers, recording confirmation for consumers and admin, price list for service and spare parts